50 philosophy classics : the greatest books distilled - Butler-Bowdon, Tom (London, United Kingdom : Nicholas Brealey Publishing, 2017)
From Aristotle to Wittgenstein and Zizek, this text provides a lively entry point to the field of philosophy. Analyses of key works show how philosophy helped shape the thinking and events of the last 150 years. It explores key writings that have shaped the discipline and impacted the real world, from ancient times, to contemporary thinkers.
Hannah Arendt : The human condition -- Aristotle Nicomachean : ethics -- A.J. Ayer Language, truth and logic -- Julian Baggini the ego trick -- Jean Baudrillard simulacra and simulation -- Simone de Beauvior the second sex -- Jeremy Bentham principles of morals and legislation -- Henri Bergson : Creative evolution -- David Bohm : wholeness and the implicate order -- Noam Chomsku : Understanding power -- Cicero on duties -- Confucius Analects -- Rene Descartes : meditations on first philosophy -- Ralph Waldo : Emerson fate -- Epicurus letters -- Michel foucault : the order of things -- Harry Frankfurt on bullshit -- Sam Harris : free will -- G.W.F. Hegel phenomenology of spirit -- Martin Heidegger : being and time -- Heraclitus fragments -- David Hume : an enquiry concerning human understanding -- William James : pragmatism -- Daniel Kahneman : thingking, fast and slo -- Immanuel Kanr : critique of pure reason -- Soren Kierkegaard : fear and trembling -- Saul Kripke : naming and necessity -- Thomas Kuhn : The structure of scientific revolutions -- Gottfried Leibniz : theodicy -- John Locke : essay concerning human understanding --
Keywords: PHILOSOPHY -- MISCELLANEA